Gut neuroendocrine signaling regulates synaptic assembly in C. elegans. (24th June 2022) - Shi, Yanjun; Qin, Lu; Wu, Mengting; Zheng, Junyu; Xie, Tao; Shao, Zhiyong
Abstract: Synaptic connections are essential to build a functional brain. How synapses are formed during development is a fundamental question in neuroscience. Recent studies provided evidence that the gut plays an important role in neuronal development through processing signals derived from gut microbes or nutrients. Defects in gut–brain communication can lead to various neurological disorders. Although the roles of the gut in communicating signals from its internal environment to the brain are well known, it remains unclear whether the gut plays a genetically encoded role in neuronal development. Using C. elegans as a model, we uncover that a Wnt‐endocrine signaling pathway in the gut regulates synaptic development in the brain. A canonical Wnt signaling pathway promotes synapse formation through regulating the expression of the neuropeptides encoding gene nlp‐40 in the gut, which functions through the neuronally expressed GPCR/AEX‐2 receptor during development. Wnt‐NLP‐40‐AEX‐2 signaling likely acts to modulate neuronal activity. Our study reveals a genetic role of the gut in synaptic development and identifies a novel contribution of the gut–brain axis. Synopsis: Wnt‐induced neuropeptide expression in the gut promotes synaptic assembly in the nerve ring of C. elegans . Canonical Wnt signaling in the gut promotes synaptic assembly in the C. elegans brain. Wnt signaling promotes the synaptic assembly by upregulating the expression of the neuropeptide NLP‐40 in the gut. NLP‐40 promotes synaptic assembly through the neuronally‐expressed GPCR receptor AEX‐2. The gut Wnt‐neuroendocrine signaling promotes synaptic formation likely through modulating neuronal activity. Abstract : Wnt‐induced neuropeptide expression in the gut promotes synaptic assembly in the nerve ring of C. elegans .